La formazione dell'immaginario borghese nell'Ottocento. Dal melodramma alla festa. Premessa per una ricerca (incompiuta) - Franco Cambi (Firenze University Press, 2011)
The history of education, from pedagogy to educational processes, has become aware of the need for this frontier of imaginary studies. Of its close relevance. Compared to the object (= education) that it also explores historically, socially and psychologically. The author has a reflection on this argument starting from the Annales, and then the social history, addressing contemporary authors about pedagogical interpretation.